• Math background
  • Math background
  • Mathematics background
  • Mathematics background
  • Fundamentals of Statistics
  • Math graphics free wallpaper in free desktop
  • stock vector : math background
  • Math background, discrete math
  • Free Math Background for Powerpoint Slides
  • Royalty-Free (RF) Clipart Illustration of a Math
  • Mathematica -photos of some famous historical figures
  • binary system
  • Pascals triangle.
  • Conic section
  • Welcome to mathematics
  • Taylor polynomials and Taylor series -
  • ... theory of Taylor series to show that the
  • The Unit Circle
  • Graphs of the functions sin(x) and cos(x),
  • GOne of the applications of the zeta function
  • Taylor Series Approximation Illustrated
  • Matematik eğitiminin sağlıklı
  • crazy math(12)
  • crazy math(11)
  • crazy math(10)
  • crazy math(9)
  • crazy math(8)
  • crazy math(7)
  • crazy math(6)
  • crazy math(5)
  • crazy math(4)
  • crazy math(3)
  • crazy math(2)
  • crazy math(1)
  • Mickeys ears are circles which are conic sections

كيفية اثبات أن مشتقة س^ن = ن س^(ن-1)

الاثنين، 19 نوفمبر، 2012 التسميات:

تستطيع اثباتها بالإستقراء الرياضى على ن .

العبارة صحيحة من أجل ن = 1  لأن مشتقة س هى 1

1 = 1س^0  حيث س لا تساوى الصفر .

نفرض أن العبارة صحيحة من أجل ن = ك

اى اننا نفرض صحة ان مشتقة س^ك = ك س^(ك-1)

والآن نبرهن على صحة العبارة عندما ن = ك+1

(س^(ك+1))  َ= (س^ك × س) َ

انت الآن بحاجة الى تطبيق قاعدة حاصل الضرب product rule

مشتقة الاول × الثانى + مشتقة الثانى × الأول

= (س^ك) َ س + س^ك

ولكن (س^ك) َ = ك س^(ك-1)     (فرضاً كما بينا)

اذاً : (س^(ك+1))  َ = ك س^(ك-1)×س + س^ك

==> نجمع الأسس لأن الأساسات متشابهة

= ك س^ك + س^ك   بأخذ س^ك عامل مشترك ...

= (ك+1) س^ك   وهو المطلوب اثباته ....... كيف ؟؟

لاحظ تبعاً للقاعدة فإن مشتقة س^(ك+1) = (ك+1) س^ك

وهذا ما حصلنا عليه، اذاً العبارة صحيحة .

ولكن ماذا لو كنا نريد الإثبات بدون استعمال قاعدة حاصل الضرب ؟

تستطيع اثبات ذلك عن طريق اللوغاريتم الطبيعى ...

نفرض أن د(س) = س^ن  بأخذ لط للطرفين ...

لط[د(س)] = ن لط(س)   نشتق الطرفين بالنسبة لـ س

    دَ(س)        ن
= ـــــــــــــ = ــــــــــ   اذاً دَ(س) س = ن د(س)
    د(س)       س

           ن د(س)     ن س^ن
دَ(س) = ــــــــــــــ = ــــــــــــــــ = ن س^(ن-1)
             س              س

وأخيراً يمكنك اثباتها عن طريق القانون العام للإشتقاق .

                        د(س+هـ) - د(س)
دَ(س) = نهـــــــــا ـــــــــــــــــــــــــــــــ
           هـ←0             هـ

0 التعليقات:

إرسال تعليق

 
mathematics problem solving © 2010 | تعريب وتطوير : سما بلوجر | Designed by Blogger Hacks | Blogger Template by ياعرب